Ultraviolet Index in the city of Puno for clear skies - Huillca Arbieto, Matías (2017)
In the highland region of Puno-Peru, the Ultraviolet Radiation Index (IUV) on the international scale are higher than normal at certain seasons of the year and reflect high risk of erythema in people, alterations in the terrestrial and aquatic ecosystem. For that reason an automatic radiometric station was installed and certified in the National University of the Altiplano, being the main objective the search of a spectral model of the IUV. We chose arbitrarily 6 days of clear sky without clouds, one day for each month from August of 2015. A good performance was demonstrated between the model and the measurements, being the correlation in average 0.99. Also the model allows to estimate the rate of ultraviolet radiation type B that is approximately 76.4% and 23.6% corresponds to type A, that is when the sun is at the zenith. On the other hand the measurements show a sinusoidal behavior noting some stability in the summer, the values Index daily maximum was on average of 14 from October until February. The dissemination of IUV data will inform, alert and sensitize the population of the harmful effects on health.